Draft Annual Plan 1988-89 Government of Goa - Planning Commission (Planning Commission, 1987)
The activities under Directorate of Animal Husbandry and Veterinary Services have been increased tremendously during the Sixth Five Year Plan(1980-85) with the undertaking of various programme in the field of development of Animal Health breeding of improved varieties of cows, demonstration farms, improved varieties of poultry birds/piggery etc. The existing infrastructure at various level will not be able, to cope up with the maintenance of the pace of development in the above sector and hence, it is found necessary to strengthen the Directorate for better planning, direction execution and evaluation of programme.
Directorate of Planning, Statistics and Evaluation Government of Goa
Directorate of Planning, Statistics and Evaluation Government of Goa